Jackson-type inequalities with generalized modulus of continuity and exact values of the n-widths of the classes of (ψ,β)-differentiable functions in L_2. II - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
In the space L_2, we determine the exact values of some n-widths for the classes of functions such that the generalized moduli of continuity of their (ψ, β) - derivatives or their averages with weight do not exceed the values of the majorants Φ satisfying certain conditions. Specific examples of realization of the obtained results are also analyzed.